Caulerpin Delivery via Pluronic-Free Cubosomes : Unlocking the Therapeutic Potential of a Pigment from an Invasive Marine Algae - Krautforst, Karolina; Kulbacka, Julita; Fornasier, Marco ; 0000-0002-5788-6741; Mocci, Rita; Porcheddu, Andrea; Pusceddu, Antonio; Moccia, Davide; Murgia, Sergio; Bazylińska, Urszula (Molecular Pharmaceutics, 2025)
Pancreatic cancer remains one of the deadliest cancers due to its resistance to conventional therapies, necessitating the development of novel treatment strategies. This study investigates the anticancer potential of caulerpin, a bisindole alkaloid derived from the invasive marine alga Caulerpa cylindracea, encapsulated in biocompatible cubosomes. Caulerpin was sustainably extracted via microwave-assisted methods and formulated into lipid-based bicontinuous cubic liquid crystalline nanoparticles using Pluronic-free surfactants (sodium taurocholate and Span 80), resulting in high encapsulation efficiency and structural stability at physiological temperature (37 °C). The formulation included cubosomes coexisting with L3 sponge nanoparticles and vesicles. In vitro studies on BxPC-3 pancreatic cancer cells demonstrated that encapsulated caulerpin significantly outperformed the free compound, inducing marked apoptotic features such as cytoskeletal disruption and cell shrinkage, as confirmed by holotomographic microscopy and F-actin bioimaging. The enhanced therapeutic efficacy is attributed to the improved protection and sustained intracellular availability of encapsulated caulerpin, which is not rapidly metabolized as in its free form. These findings suggest that caulerpin-loaded cubosomes may represent a promising nanotechnology-based strategy for pancreatic cancer treatment.
Publisher Copyright: © 2025 The Authors. Published by American Chemical Society
Keywords: algae; anticancer; caulerpin; cubosomes; nanocarriers; pancreatic tumor